2020
DOI: 10.3390/antibiotics9030106
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sitafloxacin in the Treatment of Acute Bacterial Infection: A Meta-analysis of Randomized Controlled Trials

Abstract: This meta-analysis aimed to assess the efficacy and safety of sitafloxacin in treating acute bacterial infection. PubMed, Embase, and Cochrane databases were searched up to August 13, 2019. Only randomized controlled trials (RCTs) evaluating sitafloxacin and comparators in the treatment of acute bacterial infections were included. The outcomes were clinical and microbiological responses and the risk of adverse event (AE). Five RCTs were enrolled, including 375 and 381 patients who received sitafloxacin and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… 14 , 15 , 18 In terms of safety, sitafloxacin 200 mg daily is generally well tolerated, with the most common side effects being gastrointestinal problems and liver function disorders. 19 , 20 A randomized trial comparing sitafloxacin with moxifloxacin found that the two drugs had a similar incidence of adverse effects. 19 Additionally, sitafloxacin and moxifloxacin are less associated with tendon rupture, which is an adverse effect of the second-generation quinolones 21 ; however, data on the safety of sitafloxacin are limited owing to its low availability.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 15 , 18 In terms of safety, sitafloxacin 200 mg daily is generally well tolerated, with the most common side effects being gastrointestinal problems and liver function disorders. 19 , 20 A randomized trial comparing sitafloxacin with moxifloxacin found that the two drugs had a similar incidence of adverse effects. 19 Additionally, sitafloxacin and moxifloxacin are less associated with tendon rupture, which is an adverse effect of the second-generation quinolones 21 ; however, data on the safety of sitafloxacin are limited owing to its low availability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increased resistance to quinolones throughout the world ( Tang et al, 2017 ), erythromycin (ERY) has emerged as the recommended drug for treating human campylobacteriosis ( Giannatale et al, 2019 ). Recently, sitafloxacin (SIT), a novel FQ drug, proved to be effective against various FQ-resistant pathogens including Campylobacter ( Changkwanyeun et al, 2016 ; Chen et al, 2020 ), and could be a promising drug. The persistence of FQ resistance in Campylobacter strains could be linked to the continued use of ciprofloxacin (CIP) in human medicine, international trade, travel, and use of FQs in animal husbandry along with the circulation of resistant isolates among different reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…We subsequently excluded 77 articles for the following reasons: repetitive reporting, non-randomized studies, including children, or outcomes of interest not reported. Ultimately, we included 26 meta-analyses and two new RCTs ( Salkind et al, 2002 ; Mills et al, 2005 ; Shorr et al, 2005 ; Siempos et al, 2007 ; Vardakas et al, 2008 ; Liu et al, 2010 ; Cai et al, 2011 ; Eliakim-Raz et al, 2012 ; Lei et al, 2012 ; Yuan et al, 2012 ; Jiang et al, 2013 ; Skalsky et al, 2013 ; Garin et al, 2014 ; Pakhale et al, 2014 ; Qu et al, 2015 ; Raz-Pasteur et al, 2015 ; Shen et al, 2015 ; Arthur et al, 2016 ; Horita et al, 2016 ; Kalil et al, 2016 ; O’Donnell et al, 2018 ; Lan et al, 2019 ; Liu et al, 2019 ; Rui et al, 2019 ; Sweeney and Kalil, 2019 ; Wen et al, 2019 ; Zhang et al, 2019 ; Chen et al, 2020 ).The interventions evaluated in the meta-analyses included 31 types compared of antimicrobial therapy strategies: respiratory fluoroquinolones alone, macrolides alone, β-lactams alone, macrolides+β-lactams, respiratory fluoroquinolones+β-lactams, atypical antibiotic coverage, without atypical antibiotic coverage, tigecycline, sitafloxacin, vancomycin, linezolid, teicoplanin, carbapenems, doripenem, and adjunctive nebulized antibiotics. For the included study population, 14 meta-analyses focus on CAP, while as for nosocomial pneumonia, HAP, VAP, and pneumonia, there were 6, 1, 3, and 1 meta-analyses, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five interventions assessed the clinical treatment success based on the ITT, MITT, or CE population ( Salkind et al, 2002 ; Mills et al, 2005 ; Shorr et al, 2005 ; Siempos et al, 2007 ; Vardakas et al, 2008 ; Cai et al, 2011 ; Eliakim-Raz et al, 2012 ; Lei et al, 2012 ; Yuan et al, 2012 ; Jiang et al, 2013 ; Pakhale et al, 2014 ; Raz-Pasteur et al, 2015 ; Shen et al, 2015 ; Qu et al, 2015 ; Arthur et al, 2016 ; Kalil et al, 2016 ; O’Donnell et al, 2018 ; Lan et al, 2019 ; Liu et al, 2019 ; Rui et al, 2019 ; Sweeney and Kalil, 2019 ; Wen et al, 2019 ; Zhang et al, 2019 ; Chen et al, 2020 ). Treatment with fluoroquinolones was associated with a better success rate than macrolides or β-lactam antibiotics for CAP patients in both the ITT population (RR 1.22, 95% CI: 1.02–1.47; low certainty) and CE population (RR 1.37, 95% CI: 1.11–1.68; moderate certainty).…”
Section: Resultsmentioning
confidence: 99%